PENGARUH CIRCUIT TRAINING TERHADAP KECEPATAN LARI 100 METER PADA ATLET CLUB DUMPANG ATLETIK TAHUN 2023 - Nasution, Gabe Martua; Heri, Zulfan; Hasibuan, Rosmaini (JURNAL ILMU KEOLAHRAGAAN, 2024)
This research is motivated by the lack of speed of athletes running 100 meters, seen from the component of leg muscle power also still does not have the results of poor power ability. The purpose of this study was to determine the effect of Circuit Training on 100 100-meter running Speeds at Athletic Club Dumpang Athletes in 2023. This research is experimental. The sample in this study was 10 people. The data collection technique used is by taking pre-test, treatment, and post-test. Data analysis techniques used are normality test, homogeneity test, and t-test. From the data analysis that has been done, it is known that the count value is obtained by 10.5 and table 1.83 then count (10.5> 1.83 table), so there is a significant effect of circuit training on 100-meter running speed on male athletes of the Medan athletics Dumpang club in 2023